Safety and clinical outcomes of patients treated with abiraterone acetate after docetaxel: results of the Italian Named Patient Programme. (8th October 2014) - Caffo, Orazio; De Giorgi, Ugo; Fratino, Lucia; Lo Re, Giovanni; Basso, Umberto; D'Angelo, Alessandro; Donini, Maddalena; Verderame, Francesco; Ratta, Raffaele; Procopio, Giuseppe; Campadelli, Enrico; Massari, Francesco; et al.
<x xml:space="preserve">Abstract</x> Objective To assess the safety and efficacy of abiraterone acetate (AA) in patients with metastatic castration‐resistant prostate cancer (mCRPC) treated in a compassionate named patient programme (NPP). Patients and Methods We retrospectively reviewed the clinical records of patients with mCRPC treated with AA at the standard daily oral dose of 1000 mg plus prednisone 10 mg/day in 19 Italian hospitals. Results We assessed 265 patients with mCRPC treated with AA. The most frequent (>1%) grade 3–4 toxicities were anaemia (4.2%), fatigue (4.2%), and bone pain (1.5%). The median progression‐free survival was 7 months; median overall survival was 17 months after starting AA, and 35 months after the first docetaxel administration. Our study reproduced the clinical outcomes reported in the AA pivotal trial, including those relating to special populations such as the elderly, patients with a poor performance status, symptomatic patients, and patients with visceral metastases. Conclusions Our data show the safety and activity of AA when administered outside clinical trials, and confirm the findings of the post‐docetaxel pivotal trial in the patients as a whole population and in special populations of specific interest.